Social Norms and Power Structures: Exploring Mobile Health Technologies for Maternal Healthcare in Nigeria - Udenigwe, Ogochukwu (Université d'Ottawa / University of Ottawa, 2023)
Background: Maternal and child health initiatives are embracing the use of electronic or mobile technology, a branch of digital health popularly referred to as eHealth or mHealth. While digital health can offer extensive benefits, it has raised various challenges. For instance, digital health programs are not often designed with a focus on equity in distribution nor are they designed from a gender equity standpoint. Although digital health interventions for maternal healthcare focuses predominantly on women as beneficiaries, few studies explore gendered power relations and how they impact the success of maternal and child health projects in African contexts such as Nigeria. This gap in literature risks excluding women from engaging in the digital space and can worsen the negative and unintended consequences of participating in digital health. This thesis examines the impact and implications of digital health interventions for maternal health in sub-Saharan Africa. -- Method: Two secondary and three primary studies described the various implications of digital health in sub-Saharan Africa more broadly and in rural Edo State, Nigeria, specifically. The secondary studies involved a review and a systematic review of the literature, the primary studies involved focus group discussions and in-depth interviews with pregnant or postpartum women who were beneficiaries of a digital health program and their community members. -- Results: The first paper illustrated exclusionary practices of digital health programs in sub-Saharan Africa, the second paper showed how digital health programs can challenge and redress harmful and unequal gender norms, roles, and power relations that privilege men over women. Observations from the third paper indicate that while mHealth programs are helpful to women in many ways, they are not enough on their own to undo entrenched systems of power through which men control women's reproductive lives. The fourth paper affirms that a community-centered approach to implementing digital health programs enhances women's acceptance and sustained use of digital health. The fifth paper shows how women navigate patriarchal environments through negotiation, collaboration and maneuvering to yield the best possible maternal health outcomes. -- Conclusion: At the core of all the studies was the need to understand and redress overarching factors contributing to ill health and exacerbating health inequities in maternal health through gender transformative approaches. Potentially unintended consequences, side effects, and negative effects of digital health impedes its many benefits, therefore, to achieve meaningful impact, gender and digital inclusion must remain a priority in the development, implementation, and evaluation of digital health. This thesis illuminated the needs of those with the greatest barriers to health technologies for maternal health thereby contributing to the discussion on digital health social justice with overarching themes on how to achieve equitable opportunities for all women and girls to access, use and benefit from digital health for maternal health.
Keywords: Mobile health technology; Gender; Maternal health; Sub-Saharan Africa; Digital health